2013
DOI: 10.1111/cpr.12044
|View full text |Cite
|
Sign up to set email alerts
|

Effects of bone morphogenetic protein‐4 (BMP‐4) on adipocyte differentiation from mouse adipose‐derived stem cells

Abstract: Our present study suggests that BMP-4, as an adipo-inducing factor, promoted adipogenesis of ASCs at higher concentrations (50 ng/ml) and can perhaps be considered as a candidate for use in adipose tissue engineering.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 42 publications
(55 reference statements)
2
10
0
Order By: Relevance
“…It is well known that BMP-7 is an important inducer of adipocyte differentiation [35]. In the present study, both PDL cells and DF progenitor cells showed no signs of adipocyte markers, such as LPL and PPARG.…”
Section: Gene Expressions During Differentiation Inductionsupporting
confidence: 41%
“…It is well known that BMP-7 is an important inducer of adipocyte differentiation [35]. In the present study, both PDL cells and DF progenitor cells showed no signs of adipocyte markers, such as LPL and PPARG.…”
Section: Gene Expressions During Differentiation Inductionsupporting
confidence: 41%
“…BMPs can trigger MSCs to activate transcription factors that are specific to their tissue origin in vivo, such as Pparg and Runx2, in adipogenic and osteogenic specification, respectively (Beederman et al, 2013;Wei et al, 2013). Similarly, BMP signaling activates dental pulp MSCs to express odontoblast markers (Iohara et al, 2004;Casagrande et al, 2010).…”
Section: A Bmp-regulated Transcription Factor Network Controls Odontomentioning
confidence: 99%
“…In adult organs, BMP signaling helps maintain the stem cell population size by inhibiting stem cell proliferation and niche expansion (He et al, 2004). BMP signaling activity is also required for activating MSCs to undergo differentiation in cell culture (Beederman et al, 2013;Wei et al, 2013). However, it is not clear how BMP signaling controls MSC cell fate determination during tooth root development.…”
Section: Introductionmentioning
confidence: 99%
“…13 Also, Lilja et al found that bone marrow-derived precursor cells infiltrate into adipose tissue under inflammation and become mature adipocytes; this further suggests that most of the regeneration cells that take part in adipogenesis come from recipient circulation. 20 Adipose-derived stromal cells have adipogenic ability, [21][22][23][24] and CD34 + adipose precursor cells may play an important role during adipose tissue regeneration. 25 In the threezone theory reported by Yoshimura et al, they point out that the survival of fat graft was largely determined by adipose tissue regeneration after transplantation and the CD34 + cells were very likely to be the seed cells of the adipogenic progress.…”
Section: Figmentioning
confidence: 99%